Phytoremediation of soils contaminated with heavy metals: techniques and strategies - Pinto, A.P. (2016)
Environmental pollution by heavy metals and metalloids has become a severe problem worldwide, as soils became increasingly contaminated, posing a threat to ecosystems and ultimately to human health. The decision to remediate a soil depends on the present and future value of the soil, the cost of remediation, the risk posed by the soil, and the perception of that risk by the population and decision-makers. Traditional technologies to remediate soils usually rely on excavation of the contaminated soil, often disposed of as a hazardous waste with or without a previous treatment. The use of plants to remove or immobilize toxic elements has arisen as a very promising alternative to conventional technologies. The use of plants to remediate soils derived from the observation of wild species found in specific environments, evolved to the use of fast growing crops, and later on led to the development of genetically-modified plants. Phytotechnologies include a wide range of technologies that can be applied to remediate soils through stabilization, volatilization, accumulation and sequestration of toxic metals. In this chapter we describe the impacts of heavy metals in plants and the most important phytotechnologies available to remediate soil and substrates.